Σ‐Noninnocence: Masked Phenyl‐Cation Transfer at Formal NiIV. (15th July 2019) - Steen, Jelte S.; Knizia, Gerald; Klein, Johannes E. M. N.
Abstract: Reductive elimination is an elementary organometallic reaction step involving a formal oxidation state change of −2 at a transition‐metal center. For a series of formal high‐valent Ni IV complexes, aryl–CF3 bond‐forming reductive elimination was reported to occur readily (Bour et al. J. Am. Chem. Soc . 2015, 137, 8034–8037). We report a computational analysis of this reaction and find that, unexpectedly, the formal Ni IV centers are better described as approaching a +II oxidation state, originating from highly covalent metal–ligand bonds, a phenomenon attributable to σ‐noninnocence. A direct consequence is that the elimination of aryl–CF3 products occurs in an essentially redox‐neutral fashion, as opposed to a reductive elimination. This is supported by an electron flow analysis which shows that an anionic CF3 group is transferred to an electrophilic aryl group. The uncovered role of σ‐noninnocence in metal–ligand bonding, and of an essentially redox‐neutral elimination as an elementary organometallic reaction step, may constitute concepts of broad relevance to organometallic chemistry. Abstract : Oxidationszustand? Mit theoretischen Analysen wird gezeigt, dass formale Ni IV ‐Zentren in hochvalenten Komplexen, die eine Aryl‐CF3 ‐Bindungsknüpfung durch reduktive Eliminierung bewerkstelligen, besser durch Annäherung an die Oxidationsstufe +II beschrieben werden und die Eliminierung somit weitgehend redox‐neutral ist. Der Ursprung hierfür liegt in hoch kovalenten Metall‐Ligand‐Bindungen und kann einem „nicht‐unschuldigen" σ‐Orbital zugeschrieben werden.